PENGARUH METODE DEMONSTRASI DENGAN MENGGUNAKAN ALAT PERAGA BOILER (KETEL UAP) TERHADAP PEMAHAMAN KONSEP HUKUM I TERMODINAMIKA KELAS XI DI SMA NEGERI 1 UJANMAS - Lilis Suryani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study aims to determine the effect of demonstration method by using boiler props (boiler) to understanding the concept of Law I Thermodynamics class XI in SMA Negeri 1 Ujanmas. The type of this research is quantitative description research. The population of this research is all grade XI IPA in SMA Negeri 1Ujanmas, with simple random sampling technique obtained class XI IPA 3 as control class and class XI IPA 4 as experiment class. The research instrument is a test question as much as 5 questions that are prepared based on conceptual understanding indicators. Data were analyzed using normality test, homogeneity test, and t-test. the result of the analysis was obtained, the mean value of the experimental class posttest was 78.2 and the control class 65.6. T-test of both samples for posttest with significant level α = 0.05 obtained ttable = 2.00 and tcount = 4.98 then thitung> ttable thus Ha accepted and Ho rejected. Based on the calculation of data, it can be concluded that there is a significant influence of demonstration method by using boiler props (boiler) to understanding the concept of material physics Law I thermodynamics in class XI IPA in SMA Negeri 1 Ujanmas.